DESIGN OF A MODULAR KITCHEN FURNITURE - Patricia Isabela Braileanu (Journal of Industrial Design and Engineering Graphics, 2017)
The kitchen was one of the most important rooms in the past; even if the initial houses had one room with multiple functions, in time, the kitchen got separated from the other rooms, it begins to have a certain purpose, and a well-established function. Experiencing an impressive evolution throughout the ages, the kitchen manages to become indispensable in all homes. Nowadays we see kitchens equipped with high-performance home appliances, efficient materials for furniture, easy to clean; we can also see various kitchen furniture designs, from old kitchens, which preserve a traditional tint, to eccentric and colourful kitchens with a futuristic design. If the house has ample space, then there is a large market for this kind of kitchen furniture, but what if we lack it?